2022
DOI: 10.1002/jnr.25151
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mitochondrial‐mediated mechanisms involved in oligodendrocyte development

Abstract: Oligodendrocytes are the myelinating glia of the central nervous system and are generated after oligodendrocyte progenitor cells (OPCs) transition into pre‐oligodendrocytes and then into myelinating oligodendrocytes. Myelin is essential for proper signal transmission within the nervous system and axonal metabolic support. Although the intrinsic and extrinsic factors that support the differentiation, survival, integration, and subsequent myelination of appropriate axons have been well investigated, little is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 154 publications
0
6
0
Order By: Relevance
“…White matter OPCs have a higher rate of proliferation and maturation capacity than the gray matter counterparts which are quiescent and remain in an immature state ( Dimou et al, 2008 ). OPCs have the capacity to terminally differentiate into pre-oligodendrocytes (pre-OLs), these cells either progress into myelinating OLs or undergo apoptosis ( Barres et al, 1992 ; Trapp et al, 1997 ; Back et al, 2002 ; Gil and Gama, 2023 ).…”
Section: Oligodendrocyte Fate Specification In the Developing Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…White matter OPCs have a higher rate of proliferation and maturation capacity than the gray matter counterparts which are quiescent and remain in an immature state ( Dimou et al, 2008 ). OPCs have the capacity to terminally differentiate into pre-oligodendrocytes (pre-OLs), these cells either progress into myelinating OLs or undergo apoptosis ( Barres et al, 1992 ; Trapp et al, 1997 ; Back et al, 2002 ; Gil and Gama, 2023 ).…”
Section: Oligodendrocyte Fate Specification In the Developing Cnsmentioning
confidence: 99%
“…It has been proposed that independent of myelination, oligodendrocytes provide energy metabolites such as glucose or lactate to the axons of neurons ( Lee et al, 2012 ). Oligodendrocytes are able to process glucose into pyruvate and export lactate to astrocytes and neurons which is called the astrocyte-oligodendrocyte-neuron lactate shuttle ( Philips and Rothstein, 2017 ; Gil and Gama, 2023 ). The enhanced lactate in mice is shown to increase OPC differentiation ( Ichihara et al, 2017 ).…”
Section: Interactions Of Neurons and Oligodendrocytes During Brain De...mentioning
confidence: 99%
“…Mitochondrial dysfunction is key for neurodegenerative diseases [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. Mitochondria are at the core of cellular energy production and interruption of the crosstalk between cell signaling and mitochondrial functions and biogenesis, and result in mitochondrial dysfunction, proteotoxic stress, accumulation of defective mitochondria, and the production of reactive oxygen species due to defective mitophagy and major alterations in the ubiquitin–proteasome system [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ,…”
Section: Apoe4 Brain Effectsmentioning
confidence: 99%
“…Mitochondrial dysfunction is also potentially impacted by the differences in mitochondrial DNA methylation associated with age, sex, and anatomical brain regions [ 107 ] and the capacity of glial cells, including oligodendroglia, to distribute mitochondria to subcellular locations [ 108 ]. Since myelination is an energy-consuming event, as described by Gil et al [ 108 ], oligodendrocyte development and mitochondrial-mediated mechanisms to oligodendrocyte bioenergetics and development, as well as mitochondrial development in utero are also relevant to neurodegeneration [ 109 , 110 , 111 , 112 ]. Inflammatory environments negatively impact mitochondria, as shown by Liao et al [ 113 ], using conditioned medium from LPS-activated macrophages in mice hypothalamic neurons resulting in elevated intracellular ROS/RNS levels and reduced antioxidant enzymes.…”
Section: Apoe4 Brain Effectsmentioning
confidence: 99%
“…In addition to serving as metabolic fuel for oligodendrocytes, lactate can also be used by these cells for lipid production. In vitro experiments have demonstrated that lactate can enhance the mouse OPC differentiation process [ 82 ]. When faced with low glycose availability or hypoglycemic conditions, the proliferative and differentiating capacity of oligodendrocytes is diminished, as well as an inhibition in their ability to produce myelin is introduced [ 83 ].…”
Section: Metabolic Profile Of Oligodendroglia and Myelin: A Brief Ins...mentioning
confidence: 99%